Tuft Cells and Their Role in Intestinal Diseases - Hendel, Sebastian Kjærgaard; Kellermann, Lauge; Hausmann, Annika; Bindslev, Niels; Jensen, Kim Bak; Nielsen, Ole Haagen (Frontiers in Immunology, 2022)
The interests in intestinal epithelial tuft cells, their basic physiology, involvement in immune responses and relevance for gut diseases, have increased dramatically over the last fifteen years. A key discovery in 2016 of their close connection to helminthic and protozoan infection has further spurred the exploration of these rare chemosensory epithelial cells. Although very sparse in number, tuft cells are now known as important sentinels in the gastrointestinal tract as they monitor intestinal content using succinate as well as sweet and bitter taste receptors. Upon stimulation, tuft cells secrete a broad palette of effector molecules, including interleukin-25, prostaglandin E2 and D2, cysteinyl leukotriene C4, acetylcholine, thymic stromal lymphopoietin, and β-endorphins, some of which with immunomodulatory functions. Tuft cells have proven indispensable in anti-helminthic and anti-protozoan immunity. Most studies on tuft cells are based on murine experiments using rather specific double cortin-like kinase 1-detection, while localization of human intestinal tuft cells is best performed by for instance the cyclooxygenase-1 enzyme. So far, only few studies have examined tuft cells in humans and their relation to gut disease. Here, we present an updated view on intestinal epithelial tuft cells, their physiology, immunological hub function, and their involvement in human disease. We close with a discussion on how tuft cells may have potential therapeutic value in a clinical context.